Pd nanoparticles immobilized on MIL-53(Al) as highly effective bifunctional catalysts for oxidation of liquid methanol to methyl formate - Jian-Fang Liu (KeAi Communications Co., Ltd., 2019)
Abstract A series of Pd/MIL-53(Al) heterogeneous bifunctional catalysts with different Pd contents were prepared by an impregnation method. The prepared metal–organic frameworks MIL-53(Al) and catalysts were characterized by XRD, SEM, HRTEM, FT-IR and N2 adsorption/desorption techniques. The results showed that MIL-53(Al) was synthesized successfully, and the structure was unchanged during and after the preparation of the catalysts. The Pd nanoparticles (NPs) with an average particle size of 4.6 nm were uniformly dispersed on the MIL-53(Al). The catalyst exhibited good catalytic activity in the selective oxidation of liquid methanol to methyl formate. Under the conditions of 150 °C, 2 MPa O2 and solvent-free for 5 h, the conversion of methanol could reach 60.3%, and the selectivity of methyl formate was up to 62.2%. In addition, the Pd/MIL-53(Al) bifunctional catalyst exhibited excellent stability and maintained high catalytic activity after five cycles.